2015
DOI: 10.1007/s00256-015-2126-4
|View full text |Cite
|
Sign up to set email alerts
|

Cine MRI: a new approach to the diagnosis of scapholunate dissociation

Abstract: Cine MRI of the wrist is a fast and reliable technique for the detection of SLD with diagnostic accuracy comparable to cineradiography. It can be easily implemented as a routine clinical MRI examination, facilitating diagnostic workup of patients with suspected SLD while avoiding radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Five studies [ 41 43 , 47 , 48 ] (mean QAS 69%) reported reliability using either repeated measures or multiple observers ( Table 5 ). Four studies [ 31 , 37 , 38 , 45 ] (mean QAS 74%) reported both concurrent validity and reliability using measurements on healthy volunteers (Tables 4 and 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies [ 41 43 , 47 , 48 ] (mean QAS 69%) reported reliability using either repeated measures or multiple observers ( Table 5 ). Four studies [ 31 , 37 , 38 , 45 ] (mean QAS 74%) reported both concurrent validity and reliability using measurements on healthy volunteers (Tables 4 and 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Concurrent validity and/or reliability was determined for eight dynamic MRI techniques ( Table 3 ): cine MRI [ 36 , 37 ], kinematic MRI [ 42 ], Ultrafast MRI [ 31 ], Cine Phase Contrast (PC) MRI [ 30 , 32 , 33 , 43 45 ], dynamic HASTE MRI [ 47 ], real-time MRI [ 34 , 35 , 38 , 41 , 48 ], real-time PC MRI [ 29 ], and Spin-tag or tagged MRI [ 39 , 40 , 46 ] (See S4 Appendix for a short description of each technique). The names of the sequences are reported as stated in the respective articles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Kinematic MR imaging is also being explored for the dynamic evaluation of joints for its high tissue contrast. 9 Although dedicated tools for the postprocessing of kinematic MR data have been developed, the temporal and spatial resolution interdependency of this method remains a con-siderable obstacle for its clinical application. 10,11 Finally, classic fluoroscopy is widely available and offers very high temporal and spatial resolution.…”
mentioning
confidence: 99%